The Media Spectacle of a Techno-City: COVID-19 and the South Korean Experience of the State of Emergency - Kang, Jaeho (The Journal of Asian studies, 2020)
This essay provides a critical observation of the South Korean government's distinctive management of COVID-19 with particular reference to the state of emergency. It reveals that the success of South Korea's handling of the pandemic is largely attributed by a majority of Western media to the efficient deployment of both information and communication technologies and Confucian collectivism, two components that seem contradictory yet not incompatible under the rubric of techno-Orientalism. Analyzing the intensification of surveillance and the rapid datafication of society, this essay argues that the current state of emergency is not a breakdown of normality but a continuation of the state of crisis and disaster that rules a developing country like South Korea. In doing so, the essay seeks to facilitate a critical discussion about a new mode of democracy in the era of pandemic that increasingly grapples with tensions between individual freedom and public health.